1978
DOI: 10.1104/pp.61.3.447
|View full text |Cite
|
Sign up to set email alerts
|

Rapidly Induced Wound Ethylene from Excised Segments of Etiolated Pisum sativum L., cv. Alaska

Abstract: A rapidly induced, transitory increase in the rate of ethylene synthesis occurred in wounded tissue excised from actively growing regions of etiolated barley, cucumber, maize, oat, pea, tomato, and wheat seedlings.Cutting intact stems or excising 9-mm segments of tissue from near the apex of 7-day-old etiolated Pisum sativum L., cv. Alaska seedlings induced a remarkably consistent pattern of ethylene production. At Ethylene production increases in a wide variety of plant tissues subjected to stress induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
51
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(56 citation statements)
references
References 15 publications
5
51
0
Order By: Relevance
“…If CO2 controlled wound ethylene synthesis by competing with endogenous ethylene for positive feedback sites, as it does in climacteric fruit (1, 7), then fluctuations in the internal concentration of CO2 could produce the characteristic pattern of woundinduced ethylene evolution. However, previous work has shown that during the first 2 hr, CO2 production remained almost constant as wound ethylene production fluctuated over 400%o (24).…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…If CO2 controlled wound ethylene synthesis by competing with endogenous ethylene for positive feedback sites, as it does in climacteric fruit (1, 7), then fluctuations in the internal concentration of CO2 could produce the characteristic pattern of woundinduced ethylene evolution. However, previous work has shown that during the first 2 hr, CO2 production remained almost constant as wound ethylene production fluctuated over 400%o (24).…”
Section: Methodsmentioning
confidence: 95%
“…Some experiments employed tissue which had dissipated their initial wound response (aged sections). The procedures for identifying and quantifying ethylene, C02, and 02 were the same as previously described (24 (Table I). The plungers were set at 5 ml (760 mm Hg) or held at 30 ml (130 mm Hg).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stress-induced ethylene results from de novo synthesis, via the methionine pathway (1,8), and not just from facilitated diffusion of ethylene already present in the tissue ( 16).…”
mentioning
confidence: 99%